The Impact of Narrative Persuasion on Enhancing Persuasive Effectiveness in Films: A Case Study of The Wandering Earth - Han, Xilin (Transactions on Social Science, Education and Humanities Research, 2024)
This study explores the impact of narrative persuasion in films on persuasive effectiveness, using a survey to investigate the narrative persuasion effects of the Chinese sci-fi film The Wandering Earth. The research found that the film's complex narrative structure and rich character development effectively enhance emotional resonance, making it easier for audiences to immerse themselves in the film's plot, thereby improving persuasive effectiveness. Compared to Chinese audiences, foreign audiences showed more positive story liking and character identification, and lower levels of perceived persuasive intent and persuasion resistance. This indicates different effects of the film on international audiences. This study summarizes the successful experience of The Wandering Earth in international communication, providing theoretical and practical references for understanding how films can achieve better persuasive effects in the context of globalization.